Fermentation characteristics of several carbohydrate sources for dog diets using the in vitro gas production technique - Calabrò, Serena; Carciofi, Aulus C. [UNESP]; Musco, Nadia; Tudisco, Raffaella; Gomes, Marcia O. S. [UNESP]; Cutrignelli, Monica I. (Taylor & Francis, 2012)
Fermentable carbohydrates are an important part of the canine diet. They can improve gastrointestinal health by modifying gut microbial population and metabolic activity. The present study compared the fermentation characteristics and kinetic patterns of 10 carbohydrate sources using the in vitro gas production technique (IVGPT) with dog faecal inoculum. The substrates tested were: pure cellulose (PC), carboxymethylcellulose (CMC), sugar-cane fibre (SCF), beet pulp (BP), wheat bran (WB), fructooligosaccharides (FOS), inulin, yeast cell wall (YCW), ground psyllium seed (PS), pea hulls (PH). All substrates were incubated at 39°C under anaerobic conditions with faeces collected from dogs as microbial inoculum. Gas production of fermenting cultures was recorded and after 48 h, pH, shortchain fatty acids (SCFA) and organic matter disappearance (OMD) were determined. The results confirm high fermentation by dog faecal bacteria of FOS and inulin that produced high amounts of propionate and that underwent very rapid fermentation. Three substrates (SCF, CMC and PC) were not able to support bacterial growth, with low gas and SCFA production, and high BCFA formation. The PH and BP showed moderate OMD and SCFA production. Wheat bran B underwent rapid fermentation and generated a high proportion of butyrate. Psyllium seeds underwent slow fermentation with delayed gas production, supporting a high formation of SCFA, with an adequate amount of butyrate for bacterial growth while YCW, which showed a delayed fermentation, gave moderate SCFA production. The fermentation characteristics of PS and YCW suggest their potential use in promoting a more distal fermentation on intestinal tract. © Copyright S. Calabrò et al., 2013 Licensee PAGEPress, Italy.
Keywords: Butyrate; Digestibility; Dog; Fibre; Prebiotic; Bacteria (microorganisms); Beta vulgaris subsp. vulgaris; Canis familiaris; Pisum sativum; Plantago ovata; Saccharum; Triticum aestivum